Analysis of prevalence and degree of macrocephaly in patients with germline PTEN mutations and of brain weight in Pten knock-in murine model - Mester, Jessica L (Nature Publishing Group, 2011)
PTEN Hamartoma Tumour Syndrome (PHTS) includes Cowden syndrome (CS), Bannayan-Riley-Ruvalcaba syndrome (BRRS), and other conditions resulting from germline mutation of the PTEN tumour suppressor gene. Although macrocephaly, presumably due to megencephaly, is found in both CS and BRRS, the prevalence and degree have not been formally assessed in PHTS. We evaluated head size in a prospective nested series of 181 patients found to have pathogenic germline PTEN mutations. Clinical data including occipital-frontal circumference (OFC) measurement were requested for all participants. Macrocephaly was present in 94% of 161 evaluable PHTS individuals. In patients ≤18 years, mean OFC was +4.89 standard deviations (SD) above the population mean with no difference between genders (P=0.7). Among patients >18 years, average OFC was 60.0 cm in females and 62.8 cm in males (P<0.0001). To systematically determine whether macrocephaly was due to megencephaly, we examined Pten(M3M4) missense mutant mice generated and maintained on mixed backgrounds. Mice were killed at various ages, brains were dissected out and weighed. Average brain weight for Pten(M3M4) homozygous mice (N=15) was 1.02 g compared with 0.57 g for heterozygous mice (N=29) and 0.49 g for wild-type littermates (N=24) (P<0.0001). Macrocephaly, secondary to megencephaly, is an important component of PHTS and more prevalent than previously appreciated. Patients with PHTS have increased risks for breast and thyroid cancers, and early diagnosis is key to initiating timely screening to reduce patient morbidity and mortality. Clinicians should consider germline PTEN testing at an early point in the diagnostic work-up for patients with extreme macrocephaly.